Dissipative instabilities and superradiation regimes (classic models) - Kuklin, V.M.; Poklonskiy, E.V.; Куклін, Володимир Михайлович; Поклонський, Євген Васильович (My University, 2021)
The generation of an electromagnetic field by oscillators in an open resonator is discussed in a one-dimensional approximation. In this case, the development of the so-called dissipative instability  the dissipative generation regime. Such an instability with the generation of electromagnetic oscillations arises when the decrement of oscillations in an open resonator in the absence of oscillators turns out to be greater than the increment of the resulting instability of the system of oscillators placed in this resonator. It is assumed that the oscillators do not interact with each other, and only the resonator field affects their behavior. If the resonator field is absent or small, the superradiance regime is possible, when the radiation of each oscillator is essential and the field in the system is the sum of all the eigenfields of the oscillators. In the dissipative regime of instability generation, the system of oscillators is synchronized by the induced resonator field. The synchronization of the oscillators in the superradiance mode owes its existence to the integral field of the entire system of oscillators. With a weak nonlinearity of the oscillators, a small initiating external field is required to excite the generation regime. It is noteworthy that the maximum value of the superradiance field is approximately two times less than the maximum field that the same particles could generate if they were at the same point. In all cases, for a given open resonator, the superradiance field turned out to be somewhat larger than the resonator field. Nevertheless, for the same resonator, the increments and attainable field amplitudes in both cases are of the same order of magnitude.
Дисипативні нестійкості та режими надвипромінювання (класичні моделі)
Обговорюється в одновимірному наближенні генерація електромагнітного поля осциляторами, які знаходяться у відкритому резонаторі. У цьому випадку можливий розвиток так званої дисипативної нестійкості дисипативного режиму генерації. Така нестійкість з генерацією електромагнітних коливань виникає в разі, коли декремент коливань у відкритому резонаторі у відсутності осциляторів виявляється більше інкременту виникаючої нестійкості системи осциляторів, вміщеній в цей резонатор. Передбачається, що осцилятори при цьому між собою не взаємодіють, і на їх поведінку впливає тільки резонаторне поле. Якщо ж резонаторне поле відсутнє або невелике, можливий режим надвипромінювання, коли істотне випромінювання кожного осцилятора і поле в системі є сумою всіх власних полів осциляторів. У дисипативному режимі генерації нестійкості систему осциляторів синхронізує індуковане резонаторне поле. Синхронізація осциляторів у режимі надвипромінювання зобов'язана своїм існуванням інтегральному полю всієї системи осциляторів. При слабкій нелінійності осциляторів для збудження режиму генерації необхідне невелике ініціалізуюче зовнішнє поле. Важливо, що максимальне значення поля надвипромінювання приблизно в два рази менше максимального поля, яке могли б генерувати ці ж частинки, якби вони знаходилися в одній точці. У всіх випадках для даного відкритого резонатора поле надвипромінювання виявилося трохи більшим, ніж резонаторне поле. Проте для одного і того ж резонатора інкременти і досяжні амплітуди поля в обох випадках одного порядку.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science